(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
Traveling in nature has become increasingly popular since the post-pandemic period, with Ranca Upas Campground (RUC) in Bandung being a prime destination. Visitor numbers have been steadily rising since 2019. To keep this interest alive, we must maintain the quality of the RUC’s landscape. RUC’s landscape, facilities, and infrastructure must be improved and maintained. Implementing Integrated Landscape Management (ILM), which focuses on stakeholder collaboration—including primary, supporting, and key stakeholders—is essential for effective landscape management. This mixed-method research uses focus group discussions and Likert-scale questionnaires to assess stakeholder involvement and landscape management quality at RUC, followed by in-depth interviews to understand stakeholder roles and responsibilities. The evaluation variables and indicators are based on five elements that reflect the level of stakeholder collaboration in the ILM application and Ministerial Regulation No. 24 of 2015 concerning Campground Business Standards. The evaluation results show that all variables fall into the medium-level assessment category, with only one ILM variable, collaborative planning, rated low. Based on the evaluation and interviews regarding stakeholder roles and responsibilities, strategies were developed for stakeholder engagement in nature tourism development and landscape management at RUC, enhancing environmental conservation awareness and promoting creative economy initiatives based on local wisdom to ensure its sustainability.